Self-evaluation in problem-based learning - Nabishah Mohamad; Kee, Chee Kwang; Cheng, Suh Jiuan; Lee, Sue Ann; Syazwina Mohamed; Kee, Tze Phei; Norhayati Binti Rahmat; Mohd Nasri Awang Besar (Penerbit Universiti Kebangsaan Malaysia, 2011)
Problem-based learning (PBL) was introduced to the Faculty of Medicine, Universiti Kebangsaan Malaysia (UKM), in 1987. Since then, it has been improved and has become one of the faculty’s main teaching and learning methodologies. Self-evaluation is one of the most important elements in PBL. Through self-evaluation, one is able to appraise one’s own performance in terms of strengths and identify areas for improvement. However, developing the self-evaluation skill is difficult, and there are many factors that contribute to it. This study was designed to assess the self-evaluation skill and its contributory factors among 105 first-year UKM medical students. The level of self-evaluation skill was measured by mean marks discrepancies between the final marks given by students in their self-evaluation forms and those given by facilitators in their student evaluations over four modules in the first year. Students’ perceptions of their self-evaluation skills were obtained via self-administered questionnaires. Results from this study revealed that female students have better self-evaluation skill (69%) than male students (62%), although female students tend to significantly underrate their performance while males overrate theirs. Furthermore, self-evaluation skill improves with time. In conclusion, female students are better than male students at self-evaluation.